Tussive challenge with ATP and AMP: does it reveal cough hypersensitivity?. Issue 2 (9th February 2017) - Fowles, Helen Elizabeth; Rowland, Tim; Wright, Caroline; Morice, Alyn
Recent studies have demonstrated that blockade of P2X3 ATP receptors can profoundly inhibit chronic cough. We have considered whether inhaled ATP produces a tussive response and whether chronic cough patients are hypersensitive to inhaled ATP compared to healthy volunteers. A standardised inhalational cough challenge was performed with ATP and AMP. We randomised 20 healthy volunteers and 20 chronic cough patients as to the order of challenges. The concentration of challenge solution causing at least five coughs (C5) was compared for ATP and AMP. The study population consisted of six male and 14 female volunteers in each group. Two out of 19 healthy volunteers coughed with AMP (one volunteer could not take part in this challenge) and none reached C5. Eight out of 20 chronic cough patients coughed with AMP and two reached C5. Of the 20 healthy volunteers, 18 coughed with ATP, with 15 reaching C5. All 19 chronic cough patients completing the ATP challenge coughed with ATP and 18 reached C5. The chronic cough patients had a greater cough response at lower concentrations of ATP. The greater potency of ATP versus AMP in the inhalational challenge suggests that tussive responses are mediated through members of the P2X purinergic receptor family. This acute effect was, however, not sufficient to explain cough hypersensitivity syndrome. Chronic coughers have a heightened response to ATP but not sufficient to implicate ATP in cough hypersensitivity http://ow.ly/h15730699GA